Trimetric determination of chloride ion concentration in various drinking fountains in LSU-Ozamiz - Llauder, Ma. Cristina M.; Lumosad, Josephine H.; Real, Lito A. (2011)
An analysis on the concentration of chlorides in the drinking fountain of La Salle University was done at the La Salle Chemistry Laboratory. In the analysis, the Mohr's Method which is an accurate, reliable and widely used analytical method to determine the chloride ion concentration present in drinking water was used. Results revealed that the nine (9) water samples collected in the different drinking fountains in La Salle University - Ozamiz, can be grouped into three (3) subsets. Subset 1 are those samples from drinking stations 7 and 8, subset 2 from stations 2, 3, 4, & 9; and subset 3 from stations 1, 5 & 6. It also revealed that the p value is < 0.05; there is a significant difference between the different sampling sites and their chloride ion within the drinking fountain in La Salle University - Ozamiz is less than maximum limit of 250 mg/L set by the USEPA and commercial mineral water of 80 mg/L.
Keywords: Water -- Purification -- Chlorination